Assessment of denudation rate and erosion susceptibility in the upper Tamakoshi basin in the higher Himalayas, Nepal - Timalsina, Niroj; Ghimire, Motilal (Geographical Journal of Nepal, 2021)
The higher rate of slope erosion in the Himalayan basins is contributing to rapid change in landform in the mountainous terrain, which has caused sedimentation, and inundation downstream. The Tamakoshi basin is a trans-boundary river that originates from Tibet and flows through Dolakha and Ramechap districts before joining the Sapta Koshi river. Few studies exist in Nepal attempting to quantify the erosion rate and susceptibility. However, they are scattered and mainly focus on either rill-sheet erosion or landslide only. Hence, this study attempted to estimate slope erosion by applying the Revised Universal Soil Loss Equation (RUSLE), and soil and debris erosion from landslide (2000-2019). Spatially distributed erosion intensity maps derived from the RUSLE model, as well as index-based landslide susceptibility map, were integrated to capture both running water and gravity erosion processes. The novelty of this research is that it examined the soil erosion rate using a process-based model as well as from the soil or rock displaced by the observed landslides over the last 20 years. The study estimated gross annual erosion by running water of 9.1million tons/yr, equivalent to the denudation rate of 3.34 mm/yr. Of these, landslide erosion accounts for 7.6 million ton/yr, i.e., 2.88 mm/yr, this covers about 84% of total slope erosion. High landslide and erosion potential areas are associated with high rainfall, steep slopes, scarps, lower segment of valley side slopes, high relief, and highly fractured and deformed parts of high-grade metamorphic rocks, such as gneiss, quartzite, marbles, migmatite, and granitic gneiss.